Implications of the Pagang Gadai Contract on Disharmony Social Actors in Minangkabau Community - Syukri Iska; David David; Elsy Renie; Ifelda Nengsih (Institut Agama Islam Negeri Batusangkar, 2022)
This study aims to explore the implementation of the pagang gadai contract and identify its impact on the social disharmony of actors in the Minangkabau community. The category of this research is ethnography, with data collection techniques through in-depth interviews with 13 people as resource persons who were determined based on purposive sampling and snowball sampling, located in 5 Nagari in Tanah Datar Regency, as a representation of the Nagari of origin of the Minangkabau people. The results of the study found that the implementation of pagang gadai as a form of part of debt and receivable transactions has many variants in processing and utilizing the results of the object of pawning land. Some are managed by the pawnbroker (the debtor) with some of the proceeds destined for the pawnbroker (the debtor), in addition, some are managed by the pawnbroker with the proceeds of the object being fully under his control. As for the impact on social relations, there has been disharmony, both internal to the pawnbroker and between the pawnbroker and the pawnbroker, which is caused by inconsistencies in the implementation of customary norms and rules, unequal paradigms in following up on awareness of mistakes in the implementation of pawning so far, and also because authoritarian leadership pattern on “mamak” as tribal head.